Interventions impacting the accessibility of sexual reproductive health services for head porters in sub-Saharan Africa- A scoping review protocol. - Kimberly Jarvis; Solina Richter; Samuel Adjorlolo; Michelle Swab; Eric Tenkorang; Yuping Mao; Laura A Chubb; Charles Ampong Adjei; William Midodzi; Adom Manu; Kwasi Torpey; Cara Spence; et al. (PLoS ONE, 2023)
Head porters working in markets in sub-Saharan Africa (SSA) are one of the world's most vulnerable and socioeconomically disadvantaged groups. They consist predominantly of uneducated women and girls seeking to escape poverty, early marriage, and other issues of domestic violence. Most female head porters are in their reproductive years and often lack access to sexual reproductive health services (SRHS) despite being at high risk for sexually transmitted infections (STIs), unplanned pregnancies, and gender-based violence. The low priority for women and girls' SRH in many SSA countries highlights the need to explore the factors influencing the accessibility of services for failure to do so restrains human development. An initial search of the literature was conducted and revealed no current scoping or systematic reviews on the accessibility to SRHS for female head porters in SSA. We outline a scoping review protocol, using the Joanna Briggs Institute methodology, to determine the interventions that influence the accessibility of SRHS for female head porters in SSA. The protocol is registered with Open Science Framework (https://osf.io/hjfkd). Findings will not only be valuable for female head porters but for all vulnerable female groups in SSA who experience high SRH risks and social disparities.